Peningkatan Kemampuan Belajar Siswa Melalui Pemanfaatan Aplikasi Game Quiziz - Irda Auliya Hadi Lubis; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the increase in students' learning abilities by using the quiziz application. By using a systematic literature review, search for articles related to the Quiziz application and conclude the results of the discussion of the articles found. The search for reviewed journals comes from articles/journals related to the research theme using publish or perish using the keywords